2017
DOI: 10.18805/lr.v0i0.8404
|View full text |Cite
|
Sign up to set email alerts
|

Hydropriming accelerates seed germination of Medicago sativa under stressful conditions: A thermal and hydrotime model approach

Abstract: This study determined the effects of priming on germination in response to temperature, water potential and NaCl. Thermal and hydrotime models were utilized to evaluate changes in parameters of the model after priming. Priming reduced the amount of thermal time in both cultivars, but slightly increased the base temperature for germination from 1.0 to 3.5°C in "Longdong". Priming significantly increased germination rate at high water potential but had no effect at low water potential. Further, priming reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The changes in germination percentage of alfalfa seeds were related to their priming times and boron concentration (Table 1). Germination percentage of alfalfa seeds primed with 0 boron was significantly (P<0.05) increased with the extension of times, and reached the maximum level at 9 and 12 h. This indicated that hydro-priming improved the germinating ability of alfalfa seeds, similar results was reported by Li et al (2017). Nevertheless, germination percentage of alfalfa seeds primed with other concentrations of boron all have increased firstly and then decreased with the extension of time, and germination percentage of alfalfa seeds primed with 0.1 % to 0.6 % boron was all significantly (P<0.05) higher than the control.…”
Section: Results and Discussion Effects Of Boron Priming On Germinatisupporting
confidence: 86%
“…The changes in germination percentage of alfalfa seeds were related to their priming times and boron concentration (Table 1). Germination percentage of alfalfa seeds primed with 0 boron was significantly (P<0.05) increased with the extension of times, and reached the maximum level at 9 and 12 h. This indicated that hydro-priming improved the germinating ability of alfalfa seeds, similar results was reported by Li et al (2017). Nevertheless, germination percentage of alfalfa seeds primed with other concentrations of boron all have increased firstly and then decreased with the extension of time, and germination percentage of alfalfa seeds primed with 0.1 % to 0.6 % boron was all significantly (P<0.05) higher than the control.…”
Section: Results and Discussion Effects Of Boron Priming On Germinatisupporting
confidence: 86%
“…Seed germination and seedling growth are the most critical stages that are adversely affected by stresses. Seed priming, an important technique to improve germination, involves exposure of seeds to an eliciting factor that hydrates the seed in a specific environment, followed by drying so that germination begins, but radicle emergence does not occur (Li et al, 2017 andPaparella et al, 2015). This makes the plants tolerant to future stress (Tanou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…HP of many seeds, for example, Medicago sativa (Li et al, 2017), fenugreek (Mahmoudi et al, 2019) and melon (Oliveira et al, 2019), is known to be beneficial for germination and seedling growth under salinity stress. In this study, HP of Italian ryegrass seeds resulted only in a higher GP than non-primed seeds incubated in 60 mM NaCl, but had no protective effect on root growth of 4-d-old seedlings compared with that of those from unprimed seeds incubated in 60 and 90 mM NaCl.…”
Section: Discussionmentioning
confidence: 99%